Jovens no contexto da violência e da sexualidade : estudo de caso - Nogueira, Luciana de Alcântara (2005)
A study has been accomplished concerning a group of adolescents from the municipal provisional shelter of Maringá - Paraná that presented early sexual behavior with consented or not sexual intercourse. Thus, Lukde and Andre's (1986) methodological orientation was followed for the case study. The theoretical references were Claudia Fonseca and Marcelo Medeiros's studies. The information gathering was accomplished together with the municipal provisional shelter of Maringá - Paraná during two months. We paid visits on three days during the week, at the beginning, in the middle and at the end of it. Six adolescents aging from 14 to 16 years old were the sample for this study. We interviewed the young people on different days always raising the same questions. The questions were 1) can you tell me your first sexual experience? 2) Was there approval from both sides? 3) Where did it happen? 4) Did you wear preventive condom? 5) Was the partner a boy/girlfriend or a "date"? As a result, we obtained: the six adolescents started sexual intercourse between eight and thirteen years old, usually with someone they cared for a lot. They live the friendships and the love experiences intensely to make up for their uncountable needs. The family being not structured is visible. Some of them did not even know or were raised by their parents. They suffer since their childhood the abandonment and the carelessness. Since little, they have visualized the drug utilization and traffic by the adults in their family and so they incorporate these addictions into their own lives. They endured the disintegration of their families and had to "learn how to deal with it". The six young people from the municipal provisional shelter are the picture of the social differences. They live subhuman situations, as if they were a human subspecies, seen that they do not have a family and a home for their body and mind health preservation. The speech and actions of the young people from the municipal shelter make us believe that the sexuality means for them an escape from the problems they live. They demonstrate a great interest in sex. There are no rules for the exercise of sexuality, neither an adequate age for the beginning of sexual intercourse. These adolescents, as many others that spend their lives on the streets and in institutions, did not have the same type of learning regarding sexual life as the medium class youth. It cannot be asserted that the sexuality for these young people is experienced as violence. The sexuality may be characterized, for the six young people, as a source of autonomy and almost the only source of pleasure inside the life they endure.